(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
Career maturity can be interpreted as an individual’s readiness to make decisions related to their career path, including understanding themselves, the ability to plan for the future, and skills in interacting with others in a professional environment. This study aims to determine whether there is a role of social intelligence in the career maturity of MAN students. This study uses an inferential quantitative approach. The population in this study were MAN Y students in Makassar City. This study used the Accidental Sampling technique with a sample size of 45 MAN Y students in Makassar. The instruments in this study were the career maturity scale and the social intelligence scale in the form of a Likert scale. The data analysis used was simple regression analysis. The results of the study showed a Significance value (Sig.) = 0.002, which is much smaller than 0.05 (the level of significance commonly used). This means that the regression model is statistically significant, namely social intelligence has a significant effect on career maturity. The conclusion of this study is that social intelligence plays a significant role in the career maturity of MAN Y students in Makassar City. The implications of this study for schools and guidance and counseling teachers at MAN to improve students’ social intelligence can be one of the strategic interventions in order to develop students’ career maturity from an early age